2008
DOI: 10.1080/03057640802489418
|View full text |Cite
|
Sign up to set email alerts
|

‘On the move’: primary age children in transition

Abstract: The focus of this article is the experience of the growing numbers of children who, as one of the consequences of increasing globalisation, move between cultures internationally as a result of their parents' occupations. Beginning with a review of research relating to transition, the article goes on to describe a study at an international school in Thailand which, it is argued, is similar in terms of the globally-mobile nature of its student population to many other such schools worldwide. Using a computer-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 10 publications
1
14
0
Order By: Relevance
“…This finding is supported by Meleis et al (2000), who claimed that transition experiences involve critical turning points, a period of instability, discontinuity, confusion, and distress before new beginnings and stability can occur. A similar finding is made by Dixon and Hayden (2008) supporting the same theory that unknown and unfamiliar experiences such as a new transient lifestyle can cause extreme stress, disorientation, and anxiety. In addition, the findings show that the whole family's exposure to high professional expectations was sometimes challenging.…”
Section: Discussion Of the Findingssupporting
confidence: 78%
See 1 more Smart Citation
“…This finding is supported by Meleis et al (2000), who claimed that transition experiences involve critical turning points, a period of instability, discontinuity, confusion, and distress before new beginnings and stability can occur. A similar finding is made by Dixon and Hayden (2008) supporting the same theory that unknown and unfamiliar experiences such as a new transient lifestyle can cause extreme stress, disorientation, and anxiety. In addition, the findings show that the whole family's exposure to high professional expectations was sometimes challenging.…”
Section: Discussion Of the Findingssupporting
confidence: 78%
“…Pollock and Van Reken (2001) use the expression third culture kid (TCK) which means a person of any age or nationality who has lived a significant part of their development years in one or more countries outside their passport country. Dixon and Hayden (2008) state that transitions in terms of unknown situations, such as moving to a new country or being new at school, can cause extreme stress and anxiety. According to Meleis, Sawyer, Im, Hilfinger Messias, and Schumacher (2000) most transition experiences involve a period of instability, discontinuity, confusion, and distress before a sense of stability can occur.…”
Section: Introductionmentioning
confidence: 99%
“…These changes are accompanied by changes in schools and school types (e.g., home, boarding, international, host national). Even in the national context, changing schools can result in negative social and educational consequences (Dixon & Hayden, ). Cockburn () suggested that TCKs (especially those with special needs) are vulnerable to risks related to frequent school change.…”
Section: Challenges Associated With Mk Repatriationmentioning
confidence: 99%
“…Schaetti [20] is one of the few exceptions [20][21][22][23][24] examining the expatriate children's perspective and he points out how difficult it can be to start a new life in the host country, by initially using a poem. This poem was written by a 12 year old Norwegian girl who accompanied her father to the Netherlands, where he accepted an expatriate position: This poem clearly illustrates an experience with problems in adapting to a new environment, being congruent with the results encountered in other studies [25,26].…”
Section: Expatriate Children In International Assignmentsmentioning
confidence: 99%